Efeitos da terapia de fotobiomodulação combinada ao campo magnético estático (fotomagnetoterapia) aplicada em diferentes momentos no desempenho e recuperação muscular em atletas de crossfit - Pinto, Henrique Dantas (2020)
Crossfit® is known as “Sports of Fitness”, has a training routine, called WODs (Workout of the Day), and based on the combination of functional movements, constantly varied and of high intensity. In championships, the athlete is required to complete several WODs in a sequence of days, so it is necessary for the athlete to employ strategies that aim to accelerate the muscle recovery process. The use of photobiomodulation therapy (PBMT) with low-level laser (LBP) and / or light emitting diode (LED) and the association of static magnetic field (sMF) in the post-exercise muscular physiological response have been shown to be effective in improved athletic performance. The aim of this study was to evaluate the effects of PBMT/sMF on the performance of Crossfit® athletes. A randomized, placebo-controlled, crossover and triple-blind clinical trial was conducted in which 12 athletes were submitted to an intervention protocol with effective PBMT/sMF or placebo pre and/or post WOD, totaling four different moments of application. Analyzes of athletic performance in functional testing, exertion subjective perception and physiological outcome of the intervention was analyzed. In the functional test, PBMT/sMF applied after WOD showed a difference (p<0.0001) in percentage values 48h after WOD. PBMT/sMF effective at any time was able to modulate CK release (p <0.0001) in percentage values, when compared to placebo therapy 48h after WOD, whereas the IL-6 marker had its release reduced with (p<0.0001) in the evaluation 24h after the WOD in percentage and absolute values also. PBMT/sMF was able to modulate the release of biochemical markers of muscle damage evaluated, was also able to reduce the recovery time of Crossfit® athletes who showed superior performance in the functional test when received PBMT/sMF, with an advantage for post-WOD application.